Análise dos padrões espaço-temporais das internações por diarreia e do clima nas capitais brasileiras - Marcus Fuckner; Osmar Abilio de Carvalho Junior; Helen Gurgel; Christovam Barcellos; Laurent Durieux (Confins)
Diarrhea constitutes a major public health problem in Brazil and in the world and its seasonal dynamics of occurrence is associated with environmental conditions, such as climate-related factors. This research studied the temporal pattern of hospitalizations motivated by diarrhea and gastroenteritis with presumed infectious origin (DGOIP) in 27 Brazilian capitals, monthly recorded from 1998 to 2012, as well as the rainfall and temperature patterns. It involved the preparation and interpretation of climatograms and histograms containing quarterly data and simple linear correlation analysis. The results allowed to observe that there are more defined patterns of hospitalizations prevalence, in a given period of the year, in areas where there are two well-defined seasons, rainy and dry season, and in the other regions, such as the South of Brazil, there aren’t an unique predominant pattern. The rainy season pattern was mainly related to the North and Northeast regions and the dry season pattern to the Midwest and Southeast, which assumed a change in the predominant etiology of infection, if bacterial or viral, according to the literature. The study found that factors such as seasonality and climate-related are relevant in the analysis of DGOIP occurrence patterns, and continuous observation of hospitalizations should be performed to detect changes in seasonal patterns of the disease, notably considering the wide coverage of child vaccination for rotavirus in Brazil.